2016
DOI: 10.1136/sextrans-2015-052323
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of syphilis in men who have sex with men living in rural North Wales (UK) associated with the use of social media

Abstract: The outbreak was successfully controlled. However, it is difficult to determine which of the interventions implemented were most effective. Future outbreaks should be used as an opportunity to evaluate interventions using apps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
11
2
Order By: Relevance
“…The increasing use of social media applications for finding sexual partners, particularly among MSM, has been frequently associated with increases in sexually transmitted infection (STI) despite limited evidence. Geospatial apps and websites, however, also provide an opportunity to reach key groups with public health messaging, although such campaigns need to be effectively designed to allow for an impact on outbreak control [ 39 , 41 , 42 ].…”
Section: Outbreaksmentioning
confidence: 99%
“…The increasing use of social media applications for finding sexual partners, particularly among MSM, has been frequently associated with increases in sexually transmitted infection (STI) despite limited evidence. Geospatial apps and websites, however, also provide an opportunity to reach key groups with public health messaging, although such campaigns need to be effectively designed to allow for an impact on outbreak control [ 39 , 41 , 42 ].…”
Section: Outbreaksmentioning
confidence: 99%
“…Among MSM population, some risk factors for HAV infection were identified, such as oro-anal sexual practices and digital-rectal intercourse, history of sexual contacts with anonymous sex partners, group sex and sexual promiscuity [3]. As a matter of fact, in this at-risk group, the widespread availability and use of mobile-accessible, especially geosocial networking apps for MSM facilitate anonymous sexual activities being potential drivers of recent outbreaks of HAV [13][14][15][16]. On the other hand, dating apps and websites can be an important and effective tool to promote HAV infection prevention campaigns in outbreaks, with the advantage of a range of hard-to-reach MSM seeking anonymous sex [17].…”
Section: Men Who Have Sex With Menmentioning
confidence: 99%
“…Past research has augmented reported sexual contacts with reports of social contacts from in-person interviews (2), digital social media (7), and venue attendance (8). Partner notification yields incomplete information, especially for men who have sex with men (MSM), and remains challenging (9,10). In 2006, the US Centers for Disease Control and Prevention called for "re-evaluating partner notification (PN) methods for syphilis to determine the relative effectiveness of PN strategies and to ensure that enhanced methods are implemented."…”
Section: Introductionmentioning
confidence: 99%